(untitled) (Medical Forum Monthly, 2024)
Objective: To examine the severity of lower urinary tract symptoms in men with elderly and middle ages and also determine the effect of lower urinary tract symptoms on patients quality of life. Study Design: Observational / Cross sectional study. Place and Duration of Study: This study was conducted at the Department of Urology, Ayub Medical Teaching Institute Abbottabad from January 2018 to June 2018. Materials and Methods: One hundred and eighty patients with lower urinary tract symptoms with ages 35 to 80 years were included. Patients demographic including age, residence, occupation, education and socio-economic status were recorded. Patients with severe urinary tract infection, bladder cancer, age below 35 years were excluded. Severity of lower urinary tract symptoms were examined by IPSS and bother score. Impact of lower urinary tract symptoms severity on quality of life was examined. Results: There were 110 (61.11%) patients were ages 40 to 60 years while 70 (38.89%) patients were ages above 60 years. Majority of patients had urban residency 66.67%. From 110 patients with ages <60 years, 50 (45.45%) had mild symptomatic IPSS score, 42 (38.18%) had moderate symptoms and 18 (16.36%) had severe symptoms. In patients with ages above 60, 20 (28.57%) had mild, 28 (40%) had moderate and 22 (31.43%) had severe symptoms. Very good, good and poor quality of life was associated with mild lower urinary tract symptoms, moderate lower urinary tract symptom was significantly associated with poor quality of life and severe symptoms was significantly associated with good, poor & worst quality of life (p<0.05). Patients with ages above 60 yrs had high IPSS score p-value <0.05. Conclusion: Severity of lower urinary tract symptoms is significantly associated with quality of life of patients. Patients with elderly ages had high rate of severe symptoms with poor quality of life.